Sepsis-Exacerbated Brain Dysfunction After Intracerebral Hemorrhage - Lin, Jie; Tan, Binbin; Li, Yuhong; Feng, Hua; Chen, Yujie (Frontiers in Cellular Neuroscience, 2022)
Sepsis susceptibility is significantly increased in intracerebral hemorrhage patients, owing to the immunosuppression and intestinal microbiota dysbiosis. To date, intracerebral hemorrhage with sepsis occurrence is still difficult for clinicians to deal with, and the mortality as well as long-term cognitive disability is still increasing. Actually, intracerebral hemorrhage and sepsis are mutually exacerbated via the similar pathophysiologic mechanisms, mainly consisted of systemic inflammation and circulatory dysfunction. The main consequence of these two processes is neural dysfunction and multiple organ damages, notably via oxidative stress and neurotoxic mediation under the mediation of central nervous system activation and blood-brain barrier disruption. And the comorbidity-induced multiple organ damages will produce amount of damage-associated molecular patterns and consequently exacerbate the severity of disease. At present, the prospective views are about operating artificial restriction for peripheral immune system and achieved the cross-tolerance among organs via altering immune cell composition to reduce inflammatory damage.